Application of Wudhu Therapy in Cotrolling Emotions for Patient with Violent Behavior: A Case Report - Hidayati, Nur Oktavia; Anjelina, Dina; Rafiyah, Imas (Indonesian Journal of Global Health Research, 2024)
To control emotions in patients with violent behavior, spiritual application in the form of wudhu therapy can be carried out, because wudhu therapy is a therapy that is easy to apply according to the patient's culture and religion but has not been widely applied in mental hospitals. The purpose of this study was to determine the effect of wudhu therapy on emotional control in patients who experience violent behavior problems. The method used was case report with the study sample being one patient with violent behavior at Mental Hospital X. The data collection process was carried out by interviewing, observing, and comparing the patient's medical record data. The results showed before being given the intervention, 9 (64.2%) signs and symptoms of violent behavior appeared and after being given the intervention this decreased to 1 (7.1%). Wudhu therapy nursing intervention can be provided because it is effective in controlling emotions in patients with violent behavior.